Influence of boundary conditions on free convection flow in porous medium with newtonian heating from a vertical surface - Bocharova, Anna Albertovna; Plaksina, Irina Vladimirovna (Computational Continuum Mechanics, 2011)
The system of energy and momentum conservation equations, describing a free convection flow formed near a vertical surface in a semi-infinite porous medium under third-kind boundary conditions, is considered using boundary layer approximations. Asymptotic expansions in powers of a Darcy parameter (Da) are constructed. The dependence of flow characteristics on the governing dimensionless parameters Da and is analyzed. Analytical solutions available for the entire flow domain are derived.
Keywords: free convection; porous medium; boundary layer; asymptotic expansions; Darcy parameter